Suppression of high transverse momentum D mesons in central Pb-pb collisions at √sNN=2.76TeV - Abelev, Betty; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Journal of high energy physics, 2012)
The production of the prompt charm mesons D0, D+, D*+, and their antiparticles, was measured with the ALICE detector in Pb-Pb collisions at the LHC, at a centre-of-mass energy sNN−−−√=2.76TeVsNN=2.76TeV \sqrt{{{s_{NN}}}}=2.76\;TeV per nucleon-nucleon collision. The p t-differential production yields in the range 2 < p t < 16 GeV/c at central rapidity, |y| < 0.5, were used to calculate the nuclear modification factor R AA with respect to a proton-proton reference obtained from the cross section measured at s√=7TeVs=7TeV \sqrt{s}=7\;TeV and scaled to s√=2.76TeVs=2.76TeV \sqrt{s}=2.76\;TeV . For the three meson species, R AA shows a suppression by a factor 3-4, for transverse momenta larger than 5 GeV/c in the 20% most central collisions. The suppression is reduced for peripheral collisions.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
The ALICE Collaboration: B. Abelev, O. Busch, H. Engel, P. Glässel, R. Grajcarek, N. Herrmann, T. Krawutschke, M.J. Kweon, C. Lara, D. Lohner, J. Mercado Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J. Ulrich, S. Vallero, J. Wiechula, B. Windelband, P. Zelnicek, A. Zimmermann [und weitere]
Gesehen am 30.11.2018